PENGEMBANGAN MODEL PEMBELAJARAN BAHASA INDONESIA BERBASIS PROYEK DI ERA REVOLUSI INDUSTRI 4.0 - Fitria, Yenni; Rachayu, Imma (Universitas Pendidikan Indonesia, 2019)
The Industrial Revolution Era 4.0 requires students to think creatively and critically in order to practice independent thinking. These requirements are contrary to Indonesian language learning for students of Informatics and Computer Engineering FKIP Dehasen University Bengkulu. This development research aims to develop an effective project-based Indonesian learning model so that learning is more meaningful. Development with three steps of work and data collection by observation, interview and questionnaire. Data analysis techniques are qualitative and quantitative. The results showed that 1) the implementation of the learning model